De Novo Glycine Synthesis Is Reduced in Adults With Morbid Obesity and Increases Following Bariatric Surgery - Tan, Hong Chang; Hsu, Jean W.; Tai, E Shyong; Chacko, Shaji; Wu, Vieon; Lee, Chun Fan; Kovalik, Jean-Paul; Jahoor, Farook (Frontiers in Endocrinology, 2022)
Background: Glycine is a dietary non-essential amino acid that is low in obesity and increases following bariatric surgery. However, the exact mechanism responsible remains unclear and it is unknown whether hypoglycinemia is a cause or consequence of insulin resistance. Objective: Using multiple isotopically labeled tracers, we aimed to determine the underlying kinetic changes responsible for hypoglycinemia in obesity by: 1) Comparing glycine kinetics between participants with morbid obesity (BMI ≥ 32.5 kg/m2) to those with healthy weight (BMI < 25 kg/m2), and 2) Comparing glycine kinetic changes in participants with morbid obesity after bariatric surgery. Methods: [1,2-13C2] glycine, [2,3,3-2H3] serine, and [2H5] phenylalanine were infused to compare the glycine kinetic parameters between 21 participants with morbid obesity and 21 controls with healthy weight. Participants with morbid obesity then underwent bariatric surgery and 17 were re-studied 6 months later. Data were analyzed by non-parametric methods and presented as median (interquartile range). Results: Compared to controls, participants with morbid obesity had significantly lower plasma glycine concentrations at 163 (153-171) vs. 201 (172-227) µmol/L and significantly reduced de novo glycine synthesis rate at 86.2 (64.5-111) vs.124 (103-159) µmol·kg LBM-1·h1, p < 0.001. Following surgery, body weight and insulin resistance decreased and this was accompanied by significant increases in plasma glycine concentration to 210 (191-243) µmol/L as well as the de novo glycine synthesis rate to 127 (98.3-133) µmol·kg LBM-1·h-1, p < 0.001 vs. baseline. Conclusion: Hypoglycinemia in participants with morbid obesity was associated with impaired de novo glycine synthesis. The increase in plasma glycine concentration and de novo glycine synthesis plus the marked improvement in insulin resistance after bariatric surgery suggest that hypoglycinemia may be secondary to impaired glycine synthesis because of obesity-induced insulin resistance.